Discovery of Griphophanes Grootaert & Meuffels and Nepalomyia Hollis in the Afrotropical Region with a key to Afrotropical genera of Peloropeodinae (Diptera: Dolichopodidae) - Grichanov, Igor Ya. (Zootaxa, 2010)
The formerly Oriental genus Griphophanes Grootaert & Meuffels, 1998 and mainly Oriental genus Nepalomyia Hollis, 1964, are recorded from the Afrotropical Region for the first time. Descriptions of four new species: Griphophanes congoensis sp. nov. and G. garambaensis sp. nov. from DR Congo, Nepalomyia kotrbae sp. nov. and N. reunionensis sp. nov. from Reunion are provided. A key to genera of Peloropeodinae and a key to species of Griphophanes are compiled.